Pengaruh Solvabilitas dan Likuiditas Terhadap Profitabilitas Dengan Ukuran Perusahaan Sebagai Variabel Mediasi Pada Perusahaan Yang Terdaftar Di Indeks Saham Syariah Indonesia (ISSI) - Rohmah, Rodyah Awallul; Yuliana, Indah (Jurnal Ecogen, 2024)
This research in 2020 to 2022 aims to understand the relationship between solvency and liquidity to profitability, where company size is a mediator. This methodology uses purposive sampling resulting in two hundred and ninety-three samples representing companies listed on the Indonesian sharia stock index. The criterion is that the company has experienced profit for three consecutive years, namely in 2020-2022. The data analysis methodology used in this study consists of path analysis using smart pls. The findings of data analysis show that solvency, liquidity and company size have no direct effect on profitability, solvency and liquidity have a direct effect on company size, and company size is able to mediate the effect between solvency and liquidity on profitability.